2016
DOI: 10.1002/smll.201600799
|View full text |Cite|
|
Sign up to set email alerts
|

Bubble Meets Droplet: Particle‐Assisted Reconfiguration of Wetting Morphologies in Colloidal Multiphase Systems

Abstract: Wetting phenomena are ubiquitous in nature and play key functions in various industrial processes and products. When a gas bubble encounters an oil droplet in an aqueous medium, it can experience either partial wetting or complete engulfment by the oil. Each of these morphologies can have practical benefits, and controlling the morphology is desirable for applications ranging from particle synthesis to oil recovery and gas flotation. It is known that the wetting of two fluids within a fluid medium depends on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…For example, Zhang et al reported that the addition of appropriate colloidal particles can change the wetting configurations significantly. [211] Clearly, there are many research opportunities on the fundamental understandings of oil engulfment phenomenon, especially for the systems involving high viscosity oils, which is essential not only for the improvement of oil desorption efficiency on novel UV-RAs, but also for many industrial applications, such as flotation-assisted oil recovery, contrastenhanced ultrasonography, and defoaming.…”
Section: Stimuli-responsive Absorbents For Oil Removing/recyclingmentioning
confidence: 99%
“…For example, Zhang et al reported that the addition of appropriate colloidal particles can change the wetting configurations significantly. [211] Clearly, there are many research opportunities on the fundamental understandings of oil engulfment phenomenon, especially for the systems involving high viscosity oils, which is essential not only for the improvement of oil desorption efficiency on novel UV-RAs, but also for many industrial applications, such as flotation-assisted oil recovery, contrastenhanced ultrasonography, and defoaming.…”
Section: Stimuli-responsive Absorbents For Oil Removing/recyclingmentioning
confidence: 99%
“…2d-e) are generated when γ t-r is relatively small. Herein, one of the dispersed phases having a larger interfacial force with the carrier fluid will be engulfed into the other dispersed phase, implying that for gas-liquidliquid flow bubbles are (often) encapsulated in droplets since it is energetically favorable [54].…”
Section: Article Highlightsmentioning
confidence: 99%
“…Due to the high analogy between two-phase (gas-liquid or liquid-liquid) and three-phase (gas-liquid-liquid) microflows [17], the established transport knowledge in the former case certainly sheds important light herein. It is thus expected that the balance among interfacial, inertial and viscous forces also plays an important role in determining the phase dispersion within three-phase flow through microreactors [13,23,43,50,53,54]. This implies that for designing and studying three-phase microflow, some important parameters (e.g., capillary number, Weber number and Reynolds number, the phase flow rate ratios) deserve much research attention [18,50].…”
Section: Summarized Outlookmentioning
confidence: 99%
“…Janus emulsions, because of their natural asymmetric ability in the compositions and the shapes, are often used in the fields that need asymmetry in the shape and the materials. In these Janus materials, organic-inorganic composite 11 , nanoparticles 12 , and gas bubbles 13 are often used to achieve specific functions. But the close relationship between morphologies and the components might restrict the application of specific components combination or restrict the components choice range for the specific morphology.…”
mentioning
confidence: 99%
“…The dynamical transformation from Janus to core-shell evolution is also achieved in flowing state 21 . Small particles, which could disperse at the interface of different phases, also have been used to achieve the reconfiguration of bubble core-shell structure to Janus structure 12 . From all these results, we found that the separate transformation between different Janus structures, core-shell to reverse core-shell structures, Janus to core-shell structures, or core-shell to Janus structures have been achieved by different research groups.…”
mentioning
confidence: 99%